Gereja sebagai Communio: Implementasi dalam Struktur Hukum Kanonik Pasca Konsili Vatikan II - Josep Arianto (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
The Second Vatican Council introduced the concept of the Church as communio (fellowship) which fundamentally changed the understanding of the relationship between the Pope, bishops and the faithful. This conceptual transformation had a significant impact on the legal structure of the Church, particularly in the 1983 Code of Canon Law (1983 Code), which replaced the 1917 Code of Canon Law. This study aims to analyze the implementation of communio ecclesiology in the post-Vatican II canon law structure, with an emphasis on the relationship between the Pope and bishops, the role of diocesan bishops, and the participation of the faithful in church life. Using a qualitative approach with a document study method, this research analyzes Vatican Council II and KHK 1983 documents that reflect the spirit of communio and collegiality in the Church's legal structure. The results of the analysis show that KHK 1983 expressly adopts the ecclesiology of communio by strengthening the principle of collegiality in the hierarchical relationship of the Church, as well as recognizing the involvement of the faithful in the life of the Church through pastoral councils and financial councils at the diocesan and parish levels. This research contributes to a deeper understanding of the influence of communio ecclesiology on the legal structure of the Church and its implications for church life in the modern era.